Triclosan and triclocarbon in maternal-fetal serum, urine, and amniotic fluid samples and their implication for prenatal exposure. (November 2020) - Bai, Xueyuan; Zhang, Bo; He, Yuan; Hong, Danhong; Song, Shiming; Huang, Yingyan; Zhang, Tao
Abstract: Triclosan (TCS) and Triclocarbon (TCC) are chlorinated synthetic antimicrobial agents formaternal urinelated in quantities of consumer products. However, the biomonitoring of direct exposure reflection for fetuses are rare. In this study, we determine the concentrations of TCS and TCC in paired maternal serum, cord serum, maternal urine, and amniotic fluid samples collected from a cohort of 95 expecting mother-fetal pairs in Southern China. TCS and TCC are detected widely (detection rates: >76.9%) in maternal serum, cord serum, maternal urine, and amniotic fluid samples. TCS is found to be the predominant antimicrobial agent with median concentrations in maternal serum (1.5 ng/mL) and cord serum (1.8 ng/mL) that are one order of magnitude higher than those of tcc in maternal serum (0.085 ng/mL) and cord serum (0.052 ng/mL), respectively. Cord serum concentrations of tcs and tcc correlated well with the concentrations in maternal serum, which reflect the mothers' contribution to fetal exposure. The higher median ratio of cord serum/maternal serumTCS (0.95) compared to that of cord serum/maternal serumTCC (0.53) indicates high placental transmission ability of TCS. Moreover, the facility to penetrate the placental barrier and hard to depurate characteristics lead to the long residence of TCS in the fetal environment, causing great concern over the prenatal exposure risks during the critical window of fetal development. This study provides a novel contribution by increasing existing knowledge on the exposure assessment of TCS and TCC during pregnancy through the exploration of matched maternal-fetal samples. Graphical abstract: Image 1 Highlights: The first study to document the status of TCS and TCC in mother-fetus pairs of serum, urine and amniotic fluid samples. Higher median ratio of CS/MSTCS (0.95) compared with CS/MSTCC (0.53) reveals high placental transmission ability of TCS. Low MU/MS and AF/CS ratios indicating TCS could be accumulated in fetuses. Abstract : This study indicated widely exposure of TCS and TCC in Chinese pregnant women and their fetuses as well as high placental transmission and accumulation ability in fetuses of TCS.